Pediatric COVID-19 in Argentina: a comprehensive analysis of disease and economic burden through official data and a systematic literature review - Bardach, Ariel; Ruvinsky, Silvina; Moreno, Carolina; Perelli, Lucas; Kyaw, Moe H.; Spinardi, Julia; Mendoza, Carlos Fernando; Carballo, Carolina M.; Roel, Macarena; Espinola, Natalia (Frontiers in Pediatrics, 2024)
Background: Limited data are available on the clinical impact and economic burden of COVID-19 in the pediatric population in Argentina. We aimed to estimate the disease and economic burden of COVID-19 on children and adolescents.We analyzed official national databases and conducted a supplemental systematic review of the published literature with meta-analysis in children aged 0 to 18. The period of interest was from March 2020 to August 2021, before the introduction of vaccination in this age group as a national strategic plan. In addition, we used a cost of illness analysis to estimate the direct medical costs associated with COVID-19. All costs are reported in US dollars 2023.Results: A total of 450,503 confirmed COVID-19 cases and 180 multisystem inflammatory syndrome (MIS-C) were reported in Argentina in the study period. Fourteen observational clinical studies were identified. The meta-analyses of severity level from hospital patients showed that according to different studies 15-28% of cases were asymptomatic, 68-88% were mild or moderate, and 3-10% were severe or critical. About 28% of children had an underlying disease. In addition, the estimated economic burden associated with COVID-19 was 80 million dollars and 4 million dollars corresponded to MISC.Significant impact of COVID-19 on the healthcare system and substantial economic implications for the pediatric population in Argentina were identified. The findings should help policymakers to make informed decisions and allocate resources effectively.